Prevalence and risk factors of unruptured intracranial saccular aneurysms in hospital population by 3D-TOF-MRA with VR reconstruction - Jie Shen; Jie-Wen Geng; Peng Hu; Hong-Qi Zhang (Journal of Radiation Research and Applied Sciences, 2022)
Purpose: This study aimed to analyze the prevalence and risk factors of unruptured intracranial aneurysms (UIAs) in a hospital population using 3D-TOF-MRA with VR reconstruction. Methods: This cross-sectional study included 2149 patients who underwent brain 3D-TOF-MRA at our hospital between January and December 2019. In them, complete clinical data were collected from 1541 patients. Results: 3D-TOF-MRA examination revealed UIAs in 194 patients (229 aneurysms), for a prevalence of 9%. The average size of the UIAs was 3.7 ± 1.5 mm (range, 2.0–15.5 mm). The incidence rates of UIAs in the internal carotid artery (ICA) was 72.9% (167/229), in anterior cerebral artery (ACA) was 11.4% (26/229), in middle cerebral artery (MCA) was 9.2% (21/229), and in posterior circulation was 6.5% (15/229). Clinical data were collected from 1541 patients completely. There were 158 patients with UIAs and 1383 patients without UIAs. Multivariable regression analysis suggested that age ≥60 years (OR = 1.81, 95%CI: 1.24–2.70, P = 0.003), female sex (OR = 1.50, 95%CI: 1.08–2.10, P = 0.016), and hypertension (OR = 1.55, 95%CI: 1.08–2.28, P = 0.021) were independently associated with UIAs. Conclusions: This study suggested a high prevalence (9.0%) of UIAs in a hospital population. Age, female sex, and hypertension may be independently associated with UIAs.